The management of symptomatic simple renal cysts in children - C. Koh; T. Cserni; R. Hawkes; A.P. Dickson; S. Hennayake; D.J.B. Keene (Elsevier, 2018)
Renal cysts are being increasingly diagnosed in children due to the increasing use of ultrasound scanning (USS). Most are asymptomatic, but they may present with flank pain, haematuria, palpable mass or even urinary tract infections or urosepsis. There is a wide range of management options for symptomatic cysts, the choice of which depends on patient factors as well as surgeons' preference. In this case series, we present our experience in the management of five cases of symptomatic renal cysts which have been treated in varying ways, ranging from minimally invasive procedures to drain and sclerose the cysts, to more invasive procedures to excise and deroof the cysts. Keywords: Simple renal cyst, Sclerotherapy, Symptomatic, Management, Children